Probing Vestibular Function With Frequency- Modulated Electrical Vestibular Stimulation - Janita Nissi; Otto Kangasmaa; Ilkka Laakso (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Electrical vestibular stimulation (EVS) is a non-invasive technique used to affect the vestibular system. It disturbs the sense of balance and evokes false sensations of movement by modulating the firing rate of vestibular afferents. This study used frequency-modulated EVS (FM-EVS) combined with center-of pressure (CoP) measurements to investigate the strength-frequency relationship of the stimulation and the evoked responses. CoP responses to FM-EVS were measured for ten subjects. Stimulus waveforms composed of linear chirps were compared to the evoked CoP responses, producing estimates of the highest frequencies at which EVS affected the CoP for stimulation currents of 0.75, 1.0 and 1.5 mA. Latency was calculated as the delay between the CoP response and stimulus. In situ electric field in the vestibular system was determined using fifteen high-resolution anatomical head models using the finite element method. CoP responses were evoked at up to $5.5~± ~1.1$ Hz with 0.75 mA, $8.2~± ~1.1$ Hz with 1.0 mA, and $10.5~± ~1.2$ Hz with 1.5 mA. The vestibular electric field was $175~± ~23$ mVm ${}^{-{1}}$ per 1 mA current. The average latency of the response was $86~± ~17$ ms. The results provide insight into the strength-frequency dependency for EVS-evoked motion responses with estimates for the in situ electric field strength, which can be used for the future development of human electromagnetic field exposure guidelines or the design of both EVS and transcranial electrical brain stimulation studies.